Түрік халықтары тағдыры тарихтың алапат үш иірімінде - Мырзахметұлы, М. (ҚарМУ баспасы, 2011)
В статье рассматривается вопрос о влиянии поворотных событий в истории тюркоязычных народов на становление их духовных ценностей. Особое внимание автор уделяет исследованию направлений ка- захской литературы той эпохи. Созданные в разные эпохи произведения великих мастеров становятся объектом предлагаемого анализа. В статье освещены литературно-исторические предпосылки создания выразительности художественного слова, начиная с эпохи тюркского единства и вплоть до эпохи колониализма; рассмотрены роль воспитания и познания и их влияние на историческое осознание мощности искусства слова. In article there are considered the question on influence of crucial events in history of Turkic peoples on becoming of their cultural wealth. The author of article gives special attention to directions of the Kazakh literature of that epoch. Products of great masters existed in different epoch have become an object of the analysis given in this article. There in the article are shined literary-historical preconditions of creation of expressiveness of an art of Kazakh word, since an epoch of Turkic unity and down to an epoch of colonialism. And also there is considered an influence and a role of education and cognition on historical consciousness of capacity of art of a word.